Symptoms of Anxiety Disorders and Their Relationship with Life Satisfaction among Students Threatened by Dismissal from Mu'tah University - Sami Khatatneh (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to identify the prevalence of anxiety disorders and their relationship with life satisfaction among students threatened with dismissal at Mu'tah University, as well as the extent to which anxiety disorders predict the level of life satisfaction among them. The study sample consisted of 120 male and female students from the various humanistic and scientific faculties at Mu'tah University during the 2019/2020 university year. To achieve the objectives of the study, Spielberger et al's Anxiety Scale, which was cited in Alsaraireh's study (2018), and Allaymoun's (2016) Life Satisfaction Scale were utilized after verifying the validity and reliability of the two scales. The results of the study indicated that the general prevalence of anxiety as a trait among students threatened with dismissal from the university was high, while the level of life satisfaction was medium. The results also indicated that the level of life satisfaction among those with anxiety disorders was 12%. Finally, the results showed that gender did not mediate the association between the presence of anxiety disorders and life satisfaction. In light of the results, the study concludes with recommendations including the need to develop counseling plans and group programs to reduce the anxiety levels among students threatened with dismissal from Mu'tah University.